A critical analysis of the Australian Defence Force policy on maternal health care - Maureen Montalban (Elsevier, 2017)
Abstract Objective: To critically analyse the Australian Defence Force (ADF) policy on maternal health care: Health Directive No 235 - Management of pregnant members in the Australian Defence Force. Method: Bacchi's 'What's the problem represented to be' framework was used to analyse Health Directive No 235. This paper critically examines the representation of pregnancy and birth, the resulting effects and considers alternate representations. Results: The ADF's policy on maternal healthcare considers pregnancy as a health issue that requires specialist intervention and care, also known as the medicalisation of birth. Current research emphasises women‐centred care; a model of care not contained in the ADF policy. Conclusion: The problematisation of pregnancy in the ADF restricts women's choices regarding their maternal healthcare provider. This is contrary to the healthcare rights of Australians and likely contributes to health inequalities of ADF women. Implications for public health: A research gap regarding ADF women's knowledge and wishes regarding their maternal health care has been identified. Future research can inform any alterations to the ADF policy on maternal healthcare.